Improvement of Technology for Producing Extrudates Using Protein-Vitamin Coagulate - Chaplygina , Irina; Matyushev, Vasiliy; Semenov, Alexandr (KnE Life Sciences, 2021)
Development of modern feed production imposes the need for energy-resource-saving technologies that increase the nutritional value of finished feed. The extrusion of grain and other components included in the animal feed formulation is an additional resource of high-energy feed. Of practical interest is the production of extruded feed using protein-vitamin coagulate from green mass sap. Extrusion technology enables production of a high-quality product, provides bacterial purity of feed and ensures its high safety, which determines the effective use of extrudate in rations. Studies have been carried out to improve the technology for producing extrudates from a mixture of wheat grain and protein-vitamin coagulate obtained from alfalfa sap. An experimental production line for producing extrudates using protein-vitamin coagulate is proposed. The optimal ratio of grain and protein-vitamin coagulate was determined based on the analysis of the composition and energy value of the extrudate. It is noted that the protein content in extrudates from a mixture of wheat grain and protein-vitamin coagulate is 9%–24% higher than that in extruded wheat. The metabolizable energy in such feed is 1.4–3.1% higher than that in extruded wheat. The proposed technology for extrudate production using protein-vitamin coagulate provides feed and feed components with high protein content and metabolic energy. The mixture of wheat grain and 12% protein-vitamin coagulate is found to be optimal. Extrudates obtained on the basis of the optimal ratio of components contain 17.69% protein and 14.61 MJ/kg of metabolizable energy. Keywords: extrudate, protein-vitamin coagulate, technology, mixture, feed